DDIS-11. A CK1a ACTIVATOR PENETRATES THE BRAIN, AND SHOWS EFFICACY AGAINST DRUG-RESISTANT METASTATIC MEDULLOBLASTOMA. (5th November 2018) - Rodriguez Blanco, Jezabel; Li, Bin; Long, Jun; Orthon, Darren; Ayad, Nagi; MaCrea, Heather; Roussel, Martine; Weiss, William; Capobianco, Anthony; Robbins, David
Abstract: Although most children with medulloblastoma (MB) are cured of their disease, SONIC HEDGEHOG (SHH) subgroup MB driven by TRP53 mutations is essentially lethal. Casein Kinase 1a (CK1a phosphorylates and destabilizes GLI transcription factors, thereby inhibiting the key effectors of SHH signaling. We therefore tested a second-generation CK1a activator against, TRP53 mutant, MYCN amplified MB. Our novel CK1a activator inhibited SHH activity in vitro, acting downstream of the vismodegib target SMOOTHENED (SMO), and reduced the viability of sphere cultures derived from SHH MB. SSTC3 accumulated at high levels in the brain, inhibited growth of SHH MB tumors, and blocked metastases in a genetically-engineered vismodegib-resistant mouse model of SHH MB. Importantly, SSTC3 attenuated growth and metastasis of orthotopic patient-derived TRP53 mutant, MYCN amplified, SHH subgroup MB xenografts, increasing overall survival. Thus, a CK1a agonist penetrates into the brain, and shows efficacy against metastatic TRP53 mutant MB, which are resistant to existing therapies including the SMO inhibitors currently being evaluated clinically.